Immune Cell Responses and Cytokine Profile in Intestines of Mice Infected with Trichinella spiralis - Ding, Jing; Bai, Xue; Wang, Xuelin; Shi, Haining; Cai, Xuepeng; Luo, Xuenong; Liu, Mingyuan; Liu, Xiaolei (Frontiers in Microbiology, 2017)
The intestinal phase is critical for trichinellosis caused by Trichinella spiralis (T. spiralis), as it determines both process and consequences of the disease. Several previous studies have reported that T. spiralis induces the initial predominance of a Th1 response during the intestine stage and a subsequent predominance of a Th2 response during the muscle stage. In the present study, immune cells and cytokine profile were investigated in the intestine of mice infected with T. spiralis. The results showed that the number of eosinophils, goblet cells, mucosal mast cells, and 33D1+ dendritic cells (DCs) increased during the intestinal phase of the infection. Among these, eosinophils, goblet cells, and mucosal mast cells continued to increase until 17 dpi, and the number of 33D1+ DCs increased compared to wild type; however, it did not change with the days of infection. The mRNA and protein levels of Th1 cytokines IL-2, IL-12, and IFN-γ and the Th2 cytokines IL-4, IL-5, IL-10, IL-13, and TGF-β were all increased in the tissues of the small intestine in infected mice; however, in general, Th2 cytokines increased more than Th1 cytokines. In conclusion, our findings suggest that T. spiralis infection can induce an increase of small intestine mucosal immune cells and add further evidence to show that the intestinal mucosal immune system of infected mice was induced towards mixed Th1/Th2 phenotypes with the predominance of Th2 response at the early stage of infection.